2019
DOI: 10.32598/jpcp.7.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Body Image, Self-Esteem, and Psychological Problems Among Applicants and Non-applicants of Cosmetic Surgery

Abstract: The human beings' interest in beauty and improvement of their appearance might compel them to seek for cosmetic surgery. This study aimed to compare body image, selfesteem, and psychological problems between the applicants and non-applicants of cosmetic surgery in Iran. Methods: This was a cross-sectional study. A total of 200 participants were selected for this study (including 100 applicants and 100 non-applicants of cosmetic surgery) via purposive sampling method. The questionnaires of body image, self-este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, they probably participate in exhausting sports activities, have an interest in plastic surgery, and have vomiting behaviors. In general, they concluded that adolescents, pregnant women, and each group of people in which the visual changes occur in their appearances would be exposed to the change in body image, self-esteem, depression, and anxiety (37). Since individuals with GD also experience appearance changes due to gender alteration surgery and hormone therapy, it is expected to be subject to this rule.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they probably participate in exhausting sports activities, have an interest in plastic surgery, and have vomiting behaviors. In general, they concluded that adolescents, pregnant women, and each group of people in which the visual changes occur in their appearances would be exposed to the change in body image, self-esteem, depression, and anxiety (37). Since individuals with GD also experience appearance changes due to gender alteration surgery and hormone therapy, it is expected to be subject to this rule.…”
Section: Discussionmentioning
confidence: 99%
“…Rhinoplasty is the fth top cosmetic surgery in the world [5], so that 850 thousand rhinoplasty operations were performed in the world in 2014 [3]. Over the past few decades, a surge in cosmetic surgery has taken place in Iran so that Iran is among the top 10 countries in terms of cosmetic surgeries [6]. In 2012, Iran was at the top of list of countries in terms of popularity of cosmetic surgeries.…”
Section: Introductionmentioning
confidence: 99%